METHODOLOGY FOR ENHANCING STUDENTS’ LEARNING AND INDEPENDENT STUDY SKILLS IN CLINICAL DISCIPLINES USING THE CREDIT-MODULAR EDUCATIONAL SYSTEM (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This study explored the effectiveness of a structured methodology to improve students’ academic performance and independent learning in Neonatology, implemented within the credit-modular system. A group of 135 medical students was exposed to interactive and structured learning strategies including case-based assignments, LMS integration, and weekly assessments. Their outcomes were compared with a control group of 120 students from other departments. Results showed significant improvement in knowledge, assignment completion, and satisfaction, highlighting the pedagogical value of this approach in clinical medical education.